Enhanced and Secretory Expression of Human Granulocyte Colony Stimulating Factor by Bacillus subtilis SCK6. (31st December 2015) - Bashir, Shaista; Sadaf, Saima; Ahmad, Sajjad; Akhtar, Muhammad Waheed
Abstract : This study describes a simplified approach for enhanced expression and secretion of a pharmaceutically important human cytokine, that is, granulocyte colony stimulating factor (GCSF), in the culture supernatant of Bacillus subtilis SCK6 cells. Codon optimized GCSF and pNWPH vector containing SpymwC signal sequence were amplified by prolonged overlap extension PCR to generate multimeric plasmid DNA, which was used directly to transform B. subtilis SCK6 supercompetent cells. Expression of GCSF was monitored in the culture supernatant for 120 hours. The highest expression, which corresponded to 17% of the total secretory protein, was observed at 72 hours of growth. Following ammonium sulphate precipitation, GCSF was purified to near homogeneity by fast protein liquid chromatography on a QFF anion exchange column. Circular dichroism spectroscopic analysis showed that the secondary structure contents of the purified GCSF are similar to the commercially available GCSF. Biological activity, as revealed by the regeneration of neutrophils in mice treated with ifosfamine, was also similar to the commercial preparation of GCSF. This, to our knowledge, is the first study that reports secretory expression of human GCSF in B. subtilis SCK6 with final recovery of up to 96 mg/L of the culture supernatant, without involvement of any chemical inducer.